Effect of blanching and drying treatments on quality of bamboo shoot slices. (7th September 2013) - Zheng, Jiong; Zhang, Fusheng; Song, Jiaxin; Lin, Mao; Kan, Jianquan
Summary The enzymes activity, texture, pectin, microstructure and colour change in bamboo shoots (Dendrocalamus latiflorus) were examined to evaluate the effect of blanching and drying treatments on quality of bamboo shoot slices (BSS). Peroxidase (POD), phenylalanine ammonia‐lyase and polyphenol oxidase in BSS will become completely inactive at 95 °C for 6‐, 9‐ and 12‐min blanching treatments, respectively. The hardness and protopectin (PP) content decreased after the blanching treatment. Meanwhile, the content of water‐soluble pectin increased initially and then decreased gradually during the blanching. After the blanching treatment, the L* and a* of BSS decreased, while b* increased, ΔE > 2. The hardness of rehydrated BSS decreased by 43.57% after freeze drying (FD), which, however, decreased more after hot air drying (HAD). The pectin of rehydrated BSS was also determined to explain the hardness change in BSS. The BSS acquired similar microstructure of fresh samples after FD, while microstructure of BSS was severely damaged after HAD. The colour of BSS changes significantly after drying treatment. However, FD can maintain better colour of BSS than HAD. The results may provide a reference for industrial production of BSS.